Identifying the Glaucoma Suspect - Pace, R (Canadian Journal of Optometry, 1983)
Factors to be considered in identifying patients who require additional investigation as glaucoma suspects are discussed. This includes intraocular pressure, anterior chamber, and optic disc features.